Análise bioquímica e funcional de uma metaloprotease PI (BpMPII) isolada da peçonha de Bothrops pauloensis - Achê, David Collares (2013)
Proteases are enzymes widely found in all five life being kingdoms. These proteolytic enzymes have been studied and can be used as therapeutic tools due to their actions on physiopathologic events. Metalloproteinase are hydrolytic zinc-binding dependent enzymes which interfere in physiological processes. Snake venom metalloproteinase are widely studied animal toxins. They are divided into classes (PI, PII and PIII) and PI metalloproteinase are composed of a pro-domain and a catalytic domain in its structure. In the present work, we demonstrated the biochemical and functional characteristics of a PI- metalloproteinase (BpMP-II) isolated from B. pauloensis venom. BpMP-II was purified in three chromatography steps on cation exchange resin CM-Sepharose Fast flow, filtration Sephacryl S-300 and anion exchange Capto-Q. The isolated enzyme was homogeneous on SDS-PAGE under reduction and non-reduction conditions, with a molecular weight of 23kDa determined by MALDI-TOF mass spectrometry. The isoeletric focalization demonstrated a slight acid pI (6,1) of BpMP-II. The partial sequence of protein was determined by MS/MS (MALDI-TOF/TOF) and showed high structural similarity with others SVMPs as well as a significant score match. BpMP-II showed high proteolytic activity upon azocasein and bovine fibrinogen and was inhibited by EDTA, 1,10 phenantroline and β-mercaptoethanol. Moreover, this enzyme showed stability at neutral and alkaline pH and it was inactivated at temperatures higher than 60oC. Concentrations higher than 20μg of BpMP-II was able to decrease tEnd cells viability. A slight increase in creatine kinase (CK) levels was noticed when BpMP-II was administrated an intramuscular route on mice. Therefore, the present work permitted the identification and characterization of a molecule with great therapeutic potential.